Enhancing Cost-efficiency Trade-off for Thermoelectric Air Conditioning System in Oyo State, Nigeria - Sheu, Akeem Lawal; Olaosebikan, Aremu; Suleman, Kamaldeen Olasunkanmi; Azeez, Ibraheem Abiodun; Oyeshola, Hakeem Olayinka (Fırat University, 2025)
A variable speed thermoelectric (TE) air conditioner system is developed for efficient power management using intelligent control system. The investigation adopted Variable Voltage Variable Frequency (VVVF) regulator mode of a solid state electronic conversion system with integration of AC–DC and DC–AC Converter method. The system received power from the main 230VAC source and a step-down transformer converted it to 150VAC. The bridge rectifier converted the output voltage varying DCV by regulating the frequency. The DC voltage is transformed back into AC through Pulse Width Modulation (PWM) technique. The sinusoidal waveform is formed automatically by programmed microcontroller (PIC18F4431) Insulated Gate Bipolar Transistor (IGBT) inverter that fed the air conditional compressor motor. The investigational results revealed that as the frequency declines, speed and torque drop which resulted to substantial reduction of power intake. The study reveals that 80,280kWh of energy is expended by a conventional air conditioner (CAC) in a month under steady operation while 15,624kWh is consumed by a thermoelectric air conditioner (TEAC) at the same period. This translates to energy cost of 602,100 NGN (387.51 USD) and 18,063,000 NGN (11625.27 USD) by conventional air conditioner (CAC) daily and monthly respectively while TEAC accounts for 117,180 NGN (75.42 USD) and 3,515,400 NGN (2262.50 USD) at the same period correspondingly. The energy savings cost with the developed TE drive are 484,920 NGN (312.09 USD), 14,547,600 NGN(9362.78 USD) and 174,571,200 NGN(112353.31 NGN) averagely on daily, monthly and yearly respectively. The estimated electricity in the study shows that 67% of the energy and cost bill is saved periodically using the developed TE drive likened to traditional climate control system.

Değişken hızlı termoelektrik (TE) klima sistemi, akıllı kontrol sistemi kullanılarak verimli güç yönetimi için geliştirilmiştir. Araştırmada, Değişken Gerilim Değişken Frekans (VVVF) düzenleyici modunu içeren, AC–DC ve DC–AC dönüştürücü yöntemlerinin entegre edildiği katı hal elektronik dönüşüm sistemi kullanılmıştır. Sistem, 230V AC ana güç kaynağından beslenmiş ve bir indirgeme transformatörü yardımıyla 150V AC’ye dönüştürülmüştür. Köprü doğrultucu, çıkış gerilimini frekansı düzenleyerek değişken DC gerilime dönüştürmüştür. DC gerilim, Darbe Genişlik Modülasyonu (PWM) tekniğiyle tekrar AC’ye dönüştürülerek izole kapılı bipolar transistörlü (IGBT) inverter tarafından programlanmış bir mikrodenetleyici (PIC18F4431) aracılığıyla sinüzoidal dalga formu oluşturulmuş ve klima kompresör motoruna iletilmiştir. Deneysel sonuçlar, frekans azaldıkça hız ve torkun düştüğünü ve bunun da önemli ölçüde güç tüketimini azalttığını ortaya koymuştur. Çalışma, geleneksel bir klima sisteminin (CAC) sabit çalışmada aylık 80.280 kWh enerji tükettiğini, buna karşılık termoelektrik klima sisteminin (TEAC) aynı sürede 15.624 kWh enerji tükettiğini göstermiştir. Bu, enerji maliyetlerinin geleneksel klima (CAC) için günlük 602.100 NGN (387,5 USD) ve aylık 18.063,000 NGN (11,625.27 USD) olarak hesaplanmasına karşılık, TEAC sistemi için günlük 117.180 NGN (75,42 USD) ve aylık 3.515.400 NGN (2,262.50 USD) olarak gerçekleştiğini göstermektedir. Geliştirilen TE sürücü sistemi ile günlük 484.920 NGN (312.09 USD), aylık 14.547.600 NGN (9,362.78 USD) ve yıllık 174.571.200 NGN (112,353.31 USD) tasarruf sağlanmıştır. Çalışmada tahmin edilen elektrik tüketimi, geleneksel iklimlendirme sistemine kıyasla enerji ve maliyet faturalarında %67’lik tasarruf sağlandığını göstermektedir.
Oyo Eyaleti, Nijerya’da Termoelektrik Klima Sistemi için Maliyet-Verimlilik Takasının Geliştirilmesi
Keywords: Lasers and Quantum Electronics; Lazerler ve Kuantum Elektroniği